(untitled) (Bangladesh Journal of Botany, 2015)
A total of 59 species of epizoic algae were recorded from the carapace of Emys orbicularis (Linnaeus, 1758) (Testudinata, Emydidae). Division wise distribution of the recorded algae were Cyanophyta 26, Chlorophyta 13, Euglenophyta 5 and Chrysophyta 15. Among the recorded species Phormidium ambiguum, Pseudanabaena limnetica, Chroococcus spp. and Microcystis spp. were observed intensively. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21667 Bangladesh J. Bot. 43(2): 157-161, 2014 (September)